Can perspectives toward anesthesiology be changed among undergraduate medical students? A didactic approach or self-directed learning approach - Manju Bala; Sukhinder Baidwan; Amrit Virk; Vikramjeet Arora; Sana Tafseer (Tungs’ Medical Journal)
Background: Anesthesiology is a backbone and one of the largest specialties in teaching hospitals. However, medical students’ poor perception of anesthesiology has always been a matter of concern for anesthesiologists. Objectives: This interventional study, conducted at a tertiary care institute, aimed to compare the effectiveness of didactic lectures and self-directed learning (SDL) in changing the perception of final-year undergraduate medical students toward anesthesiology. Methods: The perceptions of 93 final-year undergraduate medical students about anesthesiology were assessed using a 15-item preintervention questionnaire before randomly dividing them into two groups. The evolution, utility, and scope of anesthesiology as a specialty were taught by adopting the SDL approach to group A and traditional didactic lecture to group B. To assess any changes in their perceptions regarding anesthesiology after the intervention, the students completed the same questionnaire. Data were analyzed using the IBM Statistical Package for Social Sciences version 21. The normality of quantitative data was checked using the Kolmogorov–Smirnov test. Furthermore, student data within a group were compared using the Wilcoxon signed-rank test. Results: The mean cumulative scores significantly improved after the intervention in both groups (P = 0.001). However, when comparing the postintervention scores between group A and group B, no statistically significant difference was observed (P = 0.054). Conclusion: SDL and didactic teaching effectively improved students’ perspectives and understanding of anesthesiology.